Distribusi Jenis Lamun Dihubungkan dengan Sebaran Nutrien Perairan di Padang Lamun Teluk Awur Jepara - Ita Riniatsih (Universitas Diponegoro, 2016)
Seagrass meadow ecosystem as one of the ecosystems in coastal areas has high productivity. The production process of seagrass stands as a result of photosynthesis produces relatively high seagrass biomass. In line with the production process, seagrass litter which decays at the bottom of the water as detritus undergoes a decomposition process by decomposing bacteria. This decomposition process will produce dissolved nutrients in the waters which are then reused by seagrass for the production process. Research on the study of the distribution of seagrass species associated with the distribution of nutrients in the seagrass beds of Awur Jepara Bay has been carried out with results showing the distribution of seagrass nutrients on four stations with 3 replications each indicating that seagrass species Thalasisia hemprichii and Enhalus acoroides tend to spread to habitats with muddy sand substrate with relatively high content of organic matter. While seagrass type Cymodocea serrulata and Syringodium isoetifolium are found more in habitats with fine sand substrate. The results of laboratory analysis for the content of aquatic and sediment nutrients showed varied results with an average range between 2,006-3,276 mg / l for nitrate and 0,0025 -0,0076 mg / l for aquatic phosphate and 4,254-7,324 mg / l for nitrate. and 2,324-5,544 mg / l for marine sediment phosphate. Diversity Index, Uniformity Index and Dominance Index of seagrass showed low to moderate values, varying according to the distribution of seagrass species found at the study site. Ekosistem padang lamun sebagai salah satu ekosistem di wilayah pesisir mempunyai produktifitas yang tinggi. Proses produksi tegakan lamun sebagai hasil fotosintesa menghasilkan biomassa lamun yang relative tinggi. Sejalan dengan proses produksi tersebut, serasah lamun yang luruh di dasar perairan sebagai detritus mengalami proses dekomposisi oleh bakteri pengurai. Proses dekomposisi ini akan menghasilkan nutrien terlarut di perairan yang kemudian akan dimanfaatkan kembali oleh lamun untuk proses produksi. Penelitian tentang kajian distribusi jenis lamun yang dihubungkan dengan sebaran nutrien perairan di padang lamun Teluk Awur Jepara telah dilakukan dengan hasil yang menunjukkan sebaran nutrient lamun di empat stasiun dengan masing masing 3 kali ulangan menunjukkan bahwa lamun jenis Thalasisia hemprichii dan Enhalus acoroides cenderung menyebar pada habitat dengan substrat pasir berlumpur dengan kandungan bahan organik yang relatif tinggi.sedangkan lamun jenis Cymodocea serrulata dan Syringodium isoetifolium lebih banyak ditemukan di habitat dengan substrat pasir halus. Hasil analisa laboratorium untuk kandungan nutrient perairan dan sedimen menunjukkan hasil yang bervariasi dengan kisaran rata-rata antara 2,006-3,276 mg/l untuk nitrat dan 0,0025 -0,0076 mg/l untuk phospat perairan serta 4,254-7,324 mg/l untuk nitrat dan 2,324-5,544 mg/l untuk phospat sedimen perairan. Indeks Keanekaragaman, Indeks Keseragaman dan Indeks Dominansi lamun menunjukan nilai rendah hingga sedang, bervariasi menurut distribusi jenis lamun yang ditemukan di lokasi penelitian.